Analysis of science subject questions in class IX junior high school using Anates 4.0 computer program - Hervi, Fauziah; Afdarina, Oksa; Syamsurizal, Syamsurizal; Lufri, Lufri (Gema Wiralodra, 2023)
One of the activities to assess test quality is item analysis, which considers the general quality of the test and the quality of each item. The study was completed after tests were collected and run on all samples, and the results served as a guide for future quality improvement of the test. This study aims to analyze the validity, reliability, level of difficulty, discriminating power, and effectiveness of the distractors on Class IX Science questions at junior high school (SMP) Negeri 9 Batanghari. The data analysis technique used is a quantitative descriptive technique. This research was conducted at SMP Negeri 9 Batanghari. Class IX students of SMP Negeri 9 Batanghari were used as research subjects. The population is all class IX students at SMP Negeri 9 Batanghari, totaling 50 students. The results of this study indicate that, in terms of (1) validity, 25 items (83%) are valid, and five items (17%) are invalid. (2) Reliability: The questions have excellent reliability, with a reliability coefficient of 0.87. (3) Difficulty level: There are seven easy questions (23%), 18 moderate questions (60%), and five difficult questions. (4) The ability to discriminate the items is considered good (moderate, good, and very good) for up to 86% of the questions. (5) The quality of the distractor is considered very good for up to 100% of the questions. Therefore, this science question can be used to assess student learning outcomes at SMP Negeri 9 Batanghari because it fulfills the requirements of a learning evaluation instrument.